2005
DOI: 10.1002/pits.20104
|View full text |Cite
|
Sign up to set email alerts
|

How reliable are informal reading inventories?

Abstract: Informal Reading Inventories (IRI) are often recommended as instructionally relevant measures of reading. However, they have also been criticized for inattention to technical quality. Examination of reliability evidence in nine recently revised IRIs revealed that fewer than half report reliability. Several appear to have sufficient reliability for lower stakes decisions such as selection of classroom reading materials, but not for higher stakes purposes such as identification of reading difficulties. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Also, in comparing strong and weak comprehenders, children's grade level of functioning in reading was estimated based on several reading comprehension measures that yielded varied grade equivalent scores; data on children's independent reading levels in graded text were not available. Although tests that provide the latter kind of information such as informal reading inventories can also be problematic (Spector, 2005), this information might have helped to interpret children's book choices in relation to their reading abilities, especially for the weak comprehenders.…”
Section: Limitationsmentioning
confidence: 99%
“…Also, in comparing strong and weak comprehenders, children's grade level of functioning in reading was estimated based on several reading comprehension measures that yielded varied grade equivalent scores; data on children's independent reading levels in graded text were not available. Although tests that provide the latter kind of information such as informal reading inventories can also be problematic (Spector, 2005), this information might have helped to interpret children's book choices in relation to their reading abilities, especially for the weak comprehenders.…”
Section: Limitationsmentioning
confidence: 99%
“…(See also Nilsson [2013/this issue], which examines reliability evidence reported in 11 new and updated IRIs and makes comparisons with Spector's earlier analysis.) Spector (2005) reported that fewer than half of the IRI manuals evaluated provided reliability information, and none provided reliability data that met the criteria of the study. Her interpretations of her findings were harsh.…”
Section: Extending Heritage Characteristics Of the Irimentioning
confidence: 97%
“…Most important, although the validity of IRIs has rarely been questioned, the reliability of commercial versions has been challenged at regular intervals. For example, Spector (2005) reviewed previous studies on this topic and analyzed the reliability documentation and data in the manuals of nine IRIs published between 2000 and 2004. (See also Nilsson [2013/this issue], which examines reliability evidence reported in 11 new and updated IRIs and makes comparisons with Spector's earlier analysis.)…”
Section: Extending Heritage Characteristics Of the Irimentioning
confidence: 99%
“…IRIs' use for identifying struggling readers (e.g., Morris, Ervin, & Conrad, 1996;Warrican, 2006) and for understanding unique profiles of reading difficulties has been well established (Dewitz & Dewitz, 2003). Additionally, the QRI-4 has higher levels of reliability when compared to currently available IRIs (Spector, 2005) having, for example, interrater reliability of .99 for total miscues, .98 for explicit comprehension, and .98 for implicit comprehension and alternate form reliability (different passages at the same grade level) of .88 (Leslie & Caldwell, 2006). While we followed the recommended administration procedure of the QRI-4, we concentrated our attention on Steve's performance at the sixth grade level.…”
Section: The Selection Of Assessmentsmentioning
confidence: 97%